Peran Belajar Matematika Terhadap Konsistensi Diri Siswa (Survei Terhadap Siswa-siswi Sekolah Menengah Atas di Kabupaten Karawang Tahun 2010/2011) - Leonard Leonard; Sitta Khomsatun Supriyati (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2011)
The aim of this research is to know the influence of learning result (achievement) toward the self-consistency of the students in senior high school in Karawang. The research method wich was used in the research is survey method. The population of research are all sudents in senior high school in Karawang, West Java. Samples are taken by multi stage sampling, consisted of 120 students. The research instruments are self-consistency. Data analysis employed regretion correlation. The hypothesis testing resulted conclution: there positive correlation of studied mathematics achievement toward the self-consistency.